Delivering data and evidence to improve nutrition in India - Partnerships and Opportunities to Strengthenand Harmonize Actions for Nutrition in India (International Food Policy Research Institute, 2020)
Despite encouraging progress on nutrition outcomes in the last decade, malnutrition continues to be a major challenge in India. People across the country are affected by different forms of malnutrition, ranging from undernutrition (child stunting, wasting, anemia, and low birthweight) to overweight and obesity. Recognizing this, India has made several important policy decisions related to nutrition over the years, including the recently launched National Nutrition Mission, with high-level political commitment. Many nutrition programs include evidence-based nutrition interventions in their design, but there is still progress to be made on the reach, quality, and uptake of interventions. In addition, emerging nutrition challenges, such as overweight among children and adults, demand new areas of action and evidence to inform those actions.